Influence of long term INM practices on the distribution of aluminium fractions in Acidic Inceptisol of North Eastern Himalaya Range and their relationship with NPK content in rice (Oryza sativa) - PATRA, ABHIK; SHARMA, V K; NATH, D J; PURAKAYASTHA, T J; BARMAN, MANDIRA; KUMAR, SARVENDRA; CHOBHE, KAPIL A; ANIL, AJIN S; CHAKRABORTY, R (The Indian Journal of Agricultural Sciences, 2020)
A long-term field experiment was commenced in 2006 with rice as a test crop under long-term integrated nutrient management (INM) practices at Instructional-cum-Research (ICR) farm of the Assam Agricultural University, Assam to study the distribution of aluminium (Al) fractions and their relationship with NPK content in different parts of rice plant under acidic Inceptisol. Results indicated that exchangeable Al and strongly organically bound and interlayer Al fractions effectively decreased whileweakly organically bound Al, amorphous Al and free Al fractions increased under integrated use of enriched compost @ 2 t/ha with 25% recommended doses of NP + 100% K over rest of the treatments. In rice, the integrated use of enriched compost @ 2 t/ha with 25% recommended doses of NP + 100% K showed significant increment in N and P content in grain, husk and straw over rest of the treatments. The K content in grain (0.36%), husk (0.37%) and straw (2.03%) was also found to be highest under application of 25% recommended doses of NP + enriched compost @ 2 t/ha + 100% K as compared to other treatments. There was a highly significant negative correlation was found between exchangeable Al and strongly organically bound and interlayer Al with N, P and K content of rice. Thus, integrated use of enriched compost with reduced dose of recommended nitrogen and phosphorus of rice reduced the toxic Al fractions in an acid soil which led to enhanced N, P and K content in rice grain, husk and straw.